A daring venture [large type] - Camden, Elizabeth, 1965- (Thorndike Press, 2018)
In early 1900s New York, biochemist Doctor Rosalind Werner works to champion a water delivery technology that will fight water-borne illnesses. The fight brings her into contact, and conflict, with newly appointed Commissioner of Water, Nicholas Drake. They wage a public battle over the water controversy-- and a private war against their own attractions. When Rosaline becomes the target of an unknown enemy, the stakes may include her life.